MRI and Neuropsychological Correlates in African Americans With Hypertension and Left Ventricular Hypertrophy. (17th April 2018) - Waldron-Perrine, Brigid; Kisser, Jason E; Brody, Aaron; Haacke, E Mark; Dawood, Rachelle; Millis, Scott; Levy, Phillip
Abstract: BACKGROUND: African Americans (AAs) are at high risk for hypertension (HTN) and poor blood pressure (BP) control. Persistently elevated BP contributes to cardiovascular morbidity. White matter hyperintensities (WMHs) are a definable magnetic resonance imaging (MRI) marker of cerebrovascular injury linked to impairments in higher level thinking (i.e., executive functions), memory formation, and speed of perceptual-motor processing. METHODS: This subinvestigation evaluated neuropsychological functioning in association with WMH on brain MRIs in 23 otherwise-healthy hypertensive AAs participating in an NIH-funded study of the effects of vitamin D on BP and cardiac remodeling in AA patients 30–74 years of age with HTN and left ventricular hypertrophy. Neuropsychological assessment included psychomotor processing speed [(Symbol Digit Modality Test (SDMT) and Trail Making Test], executive functioning (Controlled Oral Word Association Test and Trail Making Test Part B), memory (Rey Auditory Verbal Learning Test), and fine motor functioning (Finger Tapping). RESULTS: Significant correlations ( P < 0.05) were found between volume of periventricular lesions and trails A ( r = 0.51) and dominant hand finger tapping speed ( r = −0.69) and between subcortical lesion volume and trails A ( r = 0.60), both dominant ( r = −0.62) and nondominant hand finger tapping speed ( r = −0.76) and oral SDMT ( r = −0.60); higher lesion volumes correlated to worse neuropsychological performance. CONCLUSIONS: Psychomotor tests including the Trail Making Test and finger tapping speed are sensitive indicators of subclinical deficits in mental processing speed and could serve as early markers of deep subcortical cerebrovascular injury in otherwise-healthy individuals with uncontrolled chronic HTN.